The Use of Accounting Judgement in the Application of Creative Accounting Policies and Practices - Preda (Simion) , Alice Mariana; Mangu (Giurea), Gabriela; Tegledi, Monica Adriana (Acta Universitatis Danubius. Œconomica, 2022)
Creative accounting emerged at the beginning of the last century in the economies of Anglo-Saxon countries to respond to the increasingly varied requirements of users of accounting information in the context of the growing complexity of economic reality. Financial interests and business pressures have led to the use of specific policies and treatments by accounting professionals to cosmetise financial statements and thus, at the limit of legality, to provide accounting information consumers with the "truth" they want. In order to present the information users want, accounting professionals draw on their specialist knowledge, accumulated experience and professional judgement, thus demonstrating their skill and expertise in handling 'figures'. This paper aims to present the role of professional judgement in the emergence and development of creative accounting in contemporary society. In this regard, it will analyse how professional judgement is used to obtain relevant information on the financial position and performance of the economic entity, premises, techniques and methods of creative accounting, all accompanied by case studies on the evaluation of financial indicators using creative accounting techniques and methods and the impact of creative methods on the decisions of users of accounting information, especially in the process of evaluating annual financial indicators.